Lives it up eaudiobook - Peirce, Lincoln (Big Nate, 2015)
Soon to be an animated series from Nickelodeon! ""Big Nate is funny, big time!""—Jeff Kinney, author of Diary of a Wimpy Kid For fans of the hilarious Diary of a Wimpy Kid series, here comes the seventh novel in the New York Times bestselling series Big Nate. BIG NATE IS LIVING IT UP! Principal Nichols wants Nate to be buddies with new kid Breckenridge Puffington III and show him around. But that's no easy task when Breckenridge is a plant-doodling total fun-sponge. There's also something strangely familiar about this guy. . . . What in the world could it be? Meet BIG NATE, Mr. Big-time Doodler and definitely NOT the teacher's pet.